The Impact of Social Media on Organizational Culture in Islamic Organizations - Ganiem, Leila Mona (Journal International Dakwah and Communication, 2024)
The increasing integration of social media into organizational communication has significantly influenced the way Islamic organizations function, interact, and uphold their cultural values. Traditional hierarchies and communication patterns in Islamic institutions are being reshaped by digital engagement, transparency, and participatory decision-making. Social media platforms provide opportunities for improving collaboration, enhancing da’wah efforts, and fostering a more dynamic organizational culture, but they also introduce challenges related to information control, ethical considerations, and maintaining Islamic identity. Understanding the impact of social media on organizational culture within Islamic institutions is essential for developing strategies that balance digital engagement with core religious and ethical principles. A qualitative research design is employed, combining in-depth interviews, content analysis of organizational social media pages, and case studies of Islamic institutions. Findings reveal that social media enhances engagement, accelerates decision-making, and fosters inclusivity within Islamic organizations. However, challenges such as misinformation, ethical dilemmas, and shifts in authority structures must be addressed to maintain organizational cohesion and adherence to Islamic values. The study concludes that Islamic organizations must strategically integrate social media while safeguarding their cultural and ethical foundations. Recommendations for optimizing social media governance and digital leadership in Islamic organizations are discussed.